Answer:
24
Step-by-step explanation:
f(n) = f(n − 1) + 3
if n = 7 => f(7) = f(7-1) + 3 = f(6) + 3
if n = 6 => f(6) = f(6-1) + 3 = f(5) + 3
if n = 5 => f(5) = f(5-1) + 3 = f(4) + 3
if n = 4 => f(4) = f(4-1) + 3 = f(3) + 3
if n = 3 => f(3) = f(3-1) + 3 = f(2) + 3
if n = 2 => f(2) = f(2-1) + 3 = f(1) + 3
if f(1) = 6 then f(2) = 9
f(3) = 12
f(4) = 15
f(5) = 18
f(6) = 21
f(7) = 24
Step-by-step explanation:
Let Andrew wage be = X
Cammi earns $20 more than Andrew So Cammi earns = 20 + X
Brenda earns $30 less than twice Andrew's wage
So she earns = 2X - 30
Their total combanied wage is $400
So Andrew + Cammi + Brenda = $400
X + 20+X + 2X-30 =400
4X - 10 =400
4X=400+10
4X=410
X= $102.5
So Andrew earns $102.5
Cammi earns $122.5
Brenda earns $175
Answer:
24.24
Step-by-step explanation:
brainlist plzzzzzzzzzzz